Recent advances progress of targeted drugs combined with radiotherapy for advanced non-small cell lung cancer: a review - Xu, Jiamin; Wang, Zhongming (Frontiers in Oncology, 2023)
Targeted drug therapy plays an important role in the clinical application of non-small cell lung cancer, especially adenocarcinoma. However, for patients with advanced disease, drug resistance after Targeted therapy, unclear target, and other reasons that cannot or do not want surgery, the combination of chemotherapy, radiotherapy, immunity, etc. is often used. The synergistic effect of targeted drugs and radiotherapy in non-small cell lung cancer has shown good clinical efficacy. This article reviews the clinical progress of targeted drug therapy combined with radiotherapy in advanced non-small cell lung cancer in recent years, in order to provide new ideas for further clinical research of this treatment mode.